Chloroplasts alter their morphology and accumulate at the pathogen interface during infection by Phytophthora infestans. (12th August 2021) - Savage, Zachary; Duggan, Cian; Toufexi, Alexia; Pandey, Pooja; Liang, Yuxi; Segretin, María Eugenia; Yuen, Lok Him; Gaboriau, David C. A.; Leary, Alexandre Y.; Tumtas, Yasin; Khandare, Virendrasinh; Ward, Andrew D.; et al.
Summary: Upon immune activation, chloroplasts switch off photosynthesis, produce antimicrobial compounds and associate with the nucleus through tubular extensions called stromules. Although it is well established that chloroplasts alter their position in response to light, little is known about the dynamics of chloroplast movement in response to pathogen attack. Here, we report that during infection with the Irish potato famine pathogen Phytophthora infestans, chloroplasts accumulate at the pathogen interface, associating with the specialized membrane that engulfs the pathogen haustorium. The chemical inhibition of actin polymerization reduces the accumulation of chloroplasts at pathogen haustoria, suggesting that this process is partially dependent on the actin cytoskeleton. However, chloroplast accumulation at haustoria does not necessarily rely on movement of the nucleus to this interface and is not affected by light conditions. Stromules are typically induced during infection, embracing haustoria and facilitating chloroplast interactions, to form dynamic organelle clusters. We found that infection‐triggered stromule formation relies on BRASSINOSTEROID INSENSITIVE 1‐ASSOCIATED KINASE 1 (BAK1)‐mediated surface immune signaling, whereas chloroplast repositioning towards haustoria does not. Consistent with the defense‐related induction of stromules, effector‐mediated suppression of BAK1‐mediated immune signaling reduced stromule formation during infection. On the other hand, immune recognition of the same effector stimulated stromules, presumably via a different pathway. These findings implicate chloroplasts in a polarized response upon pathogen attack and point to more complex functions of these organelles in plant–pathogen interactions. Significance Statement: For the first time, we show that epidermal chloroplasts are focally deployed towards the host–pathogen interface during infection by the potato blight pathogen Phytophthora infestans, implicating chloroplasts in the focal immune response against a historically and economically important disease. This study explores the spatiotemporal dynamics and changes in morphology of chloroplasts during parasitic invasion, further establishing chloroplasts as key players in the plant immune system.